(untitled) (Annals of Medical Research, 2021)
Aim: Paclitaxel is widely used in adjuvant treatment of early breast cancer and second-line treatment of metastatic breast cancer. It has been reported that transient receptor potential melastatin-2 (TRPM2) channels are expressed intensively in breast cancer and has significant effects on oxidative stress. Selenium is an essential element and has effects on reproduction, toxicity, antiaging and DNA reproduction. In this study, we aimed to reveal the role of selenium and TRPM2 channels on apoptotic effects of paclitaxel in breast cancer cells. Material and Methods: Breast cancer cells (MCF-7) were cultured and cells were divided into seven main groups. Cells were incubated with paclitaxel and selenium separately and together administrated on breast cancer cell cultures. Cell cultures incubated with TRPM2 channel antagonist anthranilic acid and stimulator cumene-hydroperoxyde. The effects of paclitaxel and selenium were invastigated on molecular pathways of apoptosis.Results: It was found that the levels of apoptosis in paclitaxel group were significantly increased in cancer cells compared to control group (p0,001).TRPM2 channel stimulator cumene-hydroperoxyde administration resulted in significantly increased apoptosis levels compared to the control group (p0.001) and it was found that in pacliatxel + selenium group the apopitosis level significantly increased compared to paclitaxel-only group (p0.001).Conclusion: As a result of our study, it has been shown that paclitaxel significantly increases apoptosis in breast cancer cells, and this effect directly related the TRPM2 channels. It was found that the application of selenium in cell culture medium in non-toxic doses increased the TRPM2 mediated apoptotic activity of paclitaxel.